Overlooked discrepancies in protocols undermine coastal restoration practices in China - Tian Xie; Zhonghua Ning; Baoshan Cui; Qiang He; Cong Chen; Zhenchang Zhu; Yujia Zhai; Guogui Chen; Qing Wang; Shanze Li; Junhong Bai; Christopher B. Craft; et al. (Communications Earth & Environment)
Abstract To improve the success of expanding ecosystem restoration efforts, technical guiding-standards are being developed in many nations. Whether these protocols have been well adopted to guide restoration practices remains unknown, especially in developing countries where policies evolve rapidly to balance socioeconomic development with ecosystem restoration. By conducting text semantic mining analyses, we reveal widespread discrepancies between China’s coastal restoration practices and protocols over the past four decades. Over 60% of executed restoration projects had no detailed technical standards to guide implementation, especially for severely degraded ecosystems. Development of these standards lagged significantly behind project implementation, was poorly enforced, and focused more on monitoring than guiding good restoration designs and adaptive management, likely undermining restoration performance. Nevertheless, current policies toward prioritizing ecosystem restoration offer opportunities to remedy this issue. Enforcing policies to ensure that practices are guided by protocols is necessary to promote coastal restoration success in China and globally as nations strive to achieve ambitious restoration targets.